(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Introduction: The sexual response in women is complex. The association of infertility and sexual dysfunction is overlapping. Objective: To find the incidence and prevalence of female sexual dysfunction in infertile females and its correlation with infertility. Material and Methods:Total of 500 patients in the age group of 24-42 years participated in the prospective study. They were assigned fertile and infertile group. Female sexual dysfunction was assessed according to FSFI questionnaire. Patients with past history of any psychiatric illness, endocrinological disorder e.g. diabetes mellitus or on antihypertensive treatment were excluded. In our study 170 (63.67%) patients in the infertile group (n=267) had female sexual dysfunction as compared to108 (46.35%) in the fertile group (n=233), which is statistically significant (P 0.0001). Most common dysfunction observed was arousal (70%) in infertile patients. Common dysfunctions observed in fertile females were desire(40%) and orgasm(40%). FSD was significantly higher in infertile females of 31-37 years age group (P 0.002), while more common in fertile females of >42years age (P< 0.0001) . Higher female sexual dysfunction was observed in illiterate infertile females (P 0.039). Amongst the pathological factors endometriosis was the statistically significant factor associated with female sexual dysfunction and infertility (P <0.0001). No significant correlation in duration of infertility or type of infertility was observed with female sexual dysfunction. Conclusions: Female sexual dysfunction as the cause or the effect should be ascertained in infertility. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(1) : 26-30